Praktik Akuntansi dalam Perspektif Pedagang Sate Bulayak di Desa Suranadi - Danieela, Aleesya Mae; Sasanti, Elin Erlina; Ridhawati, Rini (LPPM Institut Pendidikan Nusantara Global, 2025)
This study explores accounting practices among Sate Bulayak vendors in Suranadi Village, West Lombok, using a qualitative phenomenological approach with four vendors. Findings reveal these micro-entrepreneurs operate with minimal formal accounting knowledge, relying on memory-based financial management and intuitive mental accounting. Their business sustainability depends on adaptive strategies like adjusting product quantity rather than price when costs increase. Vendors define profitability through merchandise sell-through or return of initial capital without calculating comprehensive production costs, and most fail to separate business and personal finances. This research highlights the need for contextually appropriate financial literacy interventions that respect traditional knowledge while introducing basic accounting concepts, contributing to understanding informal accounting practices in Indonesia's micro-enterprise sector.